Implementasi Konsep Kaizen dalam Total Quality Management (TQM) untuk Meningkatkan Kualitas Pelayanan - Madaniyah, Madaniyah; Safaruddin, Safaruddin; Rohadi, Rohadi; Sohiron, Sohiron (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the impact of the implementation of the Kaizen concept in Total Quality Management (TQM) on improving service quality. The library method is used to collect relevant data and information on the Kaizen concept and its application in Total Quality Management (TQM) by searching various literature such as books, journals, and articles. Credible reference sources are selected through academic databases and textbooks, then analyzed and synthesized to explore the relationship between Kaizen and improving service quality. The validity of the information is maintained by cross-referencing to ensure that the conclusions drawn are based on strong and reliable evidence. This study identifies several factors that hinder the implementation of Kaizen and Total Quality Management (TQM) in Indonesia, such as lack of understanding and training, and rigid bureaucracy. Limited resources, both budget and skilled labor, are also significant obstacles. In addition, the lack of support from top management hinders the creation of a culture of continuous improvement. To successfully implement Kaizen and TQM, organizations in Indonesia need to improve understanding, simplify bureaucracy, provide adequate resources, and gain full commitment from management.